النفقة الزوجية وتقديرها لدى المحكمة الشرعية في سلانجور : دراسة فقهية تحليلية - Norhaslinda binti Mohamad Roslan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This study aims to examine maintenance of wife and how it is estimated by the Shari'a Court in the state of Selangor (Malaysia). The researcher provides a definition for maintenance of wife, reasons of paying maintenance of wife, what it covers, its characteristics and what causes its invalidation. In this study, the researcher uses the inductive and the descriptive approaches as well as the field analysis approach. She traced and reviewed the literature of old and contemporary scholars on the concept of maintenance of wife, maintenance of wife estimations, and scholars' opinions in the insolvent husband and the privileged (but not spending) husband. She collected Fiqh evidence used in the cases in Selangor Shari'a Court and analysed them in relevance to Islamic Fiqh. The findings of the study were: 1- Maintenance of wife is one of the most important things in family matters that Islam gives interest to in order to protect the happiness of a marriage; and if it is not fulfilled it may cause separation and divorce; 2- Shari'â courts assist women who do not receive maintenance in order to get their rights by law; and 3- Maintenance of wife depends on the husband's financial capabilities, the conditions of the wife and the practiced tradition. Therefore, the researcher suggests additional solutions to the problems.